CONCEPT OF BASIC EDUCATION FROM THE PERSPECTIVE OF ISLAMIC PHILOSOPHY AND GREEK PHILOSOPHY - AZHARI; Abdussalam Masykur khazik; Muhammad Azhar al fajri (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2022)
Abstract: The purpose of this study was to determine the concept of basic education from the perspective of Islamic philosophy and Greek philosophy. This type of research is library research that uses library data as the object of study in research such as books and articles as data sources. From the analysis that has been done, the results of this study indicate that the concept of basic education from the perspective of Islamic philosophy and Greek philosophy can actually go hand in hand where Greek ideas are used to develop Islamic philosophy. So that the material or its contents have something in common. Therefore, the Arabs are in direct contact with science and philosophy. In the VII to XIII centuries, Muslim intellectuals studied philosophy and science by establishing the Temple of Wisdom as a center for research, library, and translation of Greek texts. From these works, Muslim intellectuals studied and studied the thoughts of classical Greek philosophers. So the works of Greek philosophers are very helpful for Muslim philosophers in studying these works to continue to develop science. This research contributes in adding theoretical insight about the relationship between basic education and greek philosophy perspective. Keywords: education concept, Islamic philosophy, Greek philosophy